ATG16L1 negatively regulates MAVS-mediated antiviral signaling in black carp Mylopharyngodon piceus. Issue 136 (May 2023) - He, Yunfan; Peng, Yuqing; Liu, Xiaoyu; Yu, Jiamin; Du, Yuting; Li, Zhiming; Wu, Hui; Xiao, Jun; Feng, Hao
Abstract: Autophagy related 16 like 1 (ATG16L1) is a crucial component of autophagy that regulates the formation of the autophagosome. In mammals, ATG16L1 also performs important roles in immunity, including controlling viral replication and regulating innate immune signaling; however, investigation on the role of piscine ATG16L1 in immunity is rare. In this report, the ATG16L1 homolog of black carp Mylopharyngodon piceus (bcATG16L1) was cloned and identified, and its negative regulatory role in mitochondrial antiviral signaling protein (MAVS)-mediated antiviral signaling was described. The coding region of bcATG16L1 consists of 1830 nucleotides and encodes 609 amino acids, including one coiled-coil domain at the N-terminus, three low complexity region domains in the middle, and seven WD40 domains at the C-terminus. By immunofluorescence assay and immunoblotting, we found that bcATG16L1 is a cytosolic protein with a molecular weight of ∼74 kDa. In addition, over-expression of bcATG16L1 suppressed bcMAVS-mediated bcIFNa and DrIFNφ1 promoters transcriptional activity and inhibited bcMAVS-mediated antiviral activity. We further confirmed the co-localization of bcATG16L1 and bcMAVS by immunofluorescence assay and verified the protein interaction between bcATG16L1 and bcMAVS by immunoprecipitation assay. Our results report for the first time that black carp ATG16L1 suppresses MAVS-mediated antiviral signaling in teleost fish. Highlights: bcATG16L1 interacts with bcMAVS. bcATG16L1 suppresses bcMAVS-mediated activation of bcIFNa and DrIFNφ1 promoters. bcATG16L1 negatively regulates bcMAVS-mediated antiviral activity.